Exclamatives as means of exhibiting emotions in Henry James’s Washington Square: Pragmatic aspect - Lapka Olha (ExELL (Explorations in English Language and Linguistics))
The article aims to analyse exclamatives as means of expressing emotions in dialogical discourse through the Speech Acts Theory. In particular, it dwells upon the representation of the Universal Emotion by the sub-classes of speech acts on the material of Henry James’s Washington Square. For this purpose, a structural-semantic analysis, a speech acts analysis, an intentional analysis, and a statistical analysis were used in the research. The results established pragmatic regularities of using the exclamatives in the course of communication in the novel. Thus, emotions play an essential role in constructing the character’s individual features, each of them having his/her predominant emotion. In addition, the statistical analysis showed that the majority of the analysed exclamatives are used to express the emotions of anger, joy, and sadness, which are construed predominantly by expressive and representative speech acts.